The efficacy of elastic therapeutic tape variations on measures of ankle function and performance - Brogden, C. M.; Marrin, K.; Page, R. M.; Greig, M. (Physical Therapy in Sport, 2018)
Objectives: To investigate the effects of different variations of elastic therapeutic taping (ETT) on tests used to screen for ankle injury risk and function. Design: Randomized crossover. Setting: Laboratory. Participants: Twelve professional male soccer players completed three experimental trials: No tape (NT), RockTape™ (RT), and Kinesio™ Tape (KT) applied to the ankle complex. Outcome Measures: Clinical and functional ankle screening tests were used to assess the effects of ETT on measures of joint position sense, postural stability and ground reaction forces. Results: KT (P = 0.04) and RT (P = 0.01) demonstrated significant improvements in end range joint position sense. When compared to NT, RT significantly (P = 0.02) improved mid-range joint position sense at 15°, and time to complete a drop landing task. No significant differences were observed for measures of postural stability (P = 0.12) nor ground reaction force variables (P = 0.33). Conclusions: Results advocate the use of ETT for proprioceptive and functional tasks when applied to the ankles of healthy male soccer players. However, a greater number of practical and significant differences were observed when RT only was applied, indicating that practitioners may potentially advocate the use of RT for tasks requiring proprioception and functional performance.